Chusquea yungasensis (Bambusoideae, Poaceae): a new species of woody bamboo from South America and the first record of subgenus Rettbergia in Bolivia - Mota, Aline Costa; Pérez, Iván Jiménez; Oliveira, Reyjane Patrícia De; Clark, Lynn (Phytotaxa, 2014)
A new species of Chusquea subg. Rettbergia is described, illustrated and compared with C. bambusoides. Chusquea yungasensis sp. nov. differs from other species of subg. Rettbergia by its racemose synflorescences. The new species is endemic to Bolivia, and found only in the Yungas ecoregion. Although this subgenus is exclusive to South America, this new species represents the first record of the group in Bolivia.